Identification of cut-off value for homeostatic model assessment for insulin resistance in children at a tertiary care hospital in Bangladesh - Jahan, Ismat; Sharmin, Farzana; Parvin, Roksana; Rezaul Karim, Muhammad; Biswas, Diraj Chandra; Begum, Suraiya (International Journal of Contemporary Pediatrics, 2025)
Background: Insulin resistance (IR) is associated with obesity, type 2 diabetes, dyslipidemia, hypertension, atherosclerosis, polycystic ovary syndrome, and non-alcoholic fatty liver disease. In recent years, IR has been increasingly reported in children. Among surrogate indices, the homeostatic model assessment of IR (HOMA-IR) is the most widely used. Methods: A cross-sectional study was conducted at Bangladesh medical university, involving 613 children aged 6-18 years. Fasting insulin, glucose, and lipid profiles were measured, and HOMA-IR was calculated. Optimal cut-off values for IR were determined using percentile and modified ATP III metabolic syndrome criteria. Diagnostic accuracy was assessed using sensitivity, specificity, and the Youden index. Results: HOMA-IR cut-off values at the 85th percentile ranged from 2.3 to 2.6, and by metabolic syndrome criteria from 2.0 to 2.4, with high sensitivity (93.2%) and specificity (60.1%). At the 95th percentile, cut-offs were higher (3.0-4.7) but less sensitive (78.6%) and specific (72.9%). A value of 2.4 was consistent across both approaches. Conclusions: This study recommends 2.4 as optimal HOMA-IR cut-off for diagnosing IR in Bangladeshi children.